Respuesta:
Simplifying
x + -3 = -13
Reorder the terms:
-3 + x = -13
Solving
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + 3 + x = -13 + 3
Combine like terms: -3 + 3 = 0
0 + x = -13 + 3
x = -13 + 3
Combine like terms: -13 + 3 = -10
x = -10
Explicación paso a paso: YIAP CORONITA SHI
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
Simplifying
x + -3 = -13
Reorder the terms:
-3 + x = -13
Solving
-3 + x = -13
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + 3 + x = -13 + 3
Combine like terms: -3 + 3 = 0
0 + x = -13 + 3
x = -13 + 3
Combine like terms: -13 + 3 = -10
x = -10
Simplifying
x = -10
Explicación paso a paso: YIAP CORONITA SHI